Children Hospitalized for Varicella: Complications and Cost Burden. - Turel, Ozden; Bakir, Mustafa; Gonen, Ismail; Hatipoglu, Nevin; Aydogmus, Cigdem; Hosaf, Emine; Siraneci, Rengin (My University, 2023)
To evaluate the direct medical cost of hospital admissions for patients with varicella (i.e., chickenpox) to assess the cost burden of varicella from a health care perspective for ultimate use in health economics studies in Turkey.

Records of children hospitalized with varicella at the Bakirkoy Maternity and Children's Hospital between November of 2006 and June of 2011 were reviewed. Reasons for hospitalization, types of varicella-associated complications, and direct medical cost of hospitalization were noted. Patients with underlying risk factors were excluded. Data obtained from one hospital were used to estimate the national cost of the disease.

During the 4.5-year study period, 234 patients were hospitalized with varicella. Of these cases, 48 (20%) children previously ill with underlying cancers or chronic diseases were excluded from the study. Ultimately, 186 previously healthy children (age range: 14 days to 159 months, median age: 14 months) were included. The main reasons for hospitalization were complications related to varicella (79%), the most frequent of which was skin and soft tissue infections, followed by neurological complications and pneumonia. The median cost of hospitalization per patient was US $283, 50% of which was attributed to medication costs. The annual cost for varicella hospitalizations in Turkey was estimated at US $396,200.

A significant number of healthy children are hospitalized for varicella and associated complications. Descriptions of these complications and their related costs provide important data for cost-effectiveness studies for decisions about the inclusion of the varicella vaccine in a childhood vaccination program.
Keywords: child; complications; cost; varicella